2012
DOI: 10.1093/nar/gks1070
|View full text |Cite
|
Sign up to set email alerts
|

Purification of DNA-origami nanostructures by rate-zonal centrifugation

Abstract: Most previously reported methods for purifying DNA-origami nanostructures rely on agarose-gel electrophoresis (AGE) for separation. Although AGE is routinely used to yield 0.1–1 µg purified DNA nanostructures, obtaining >100 µg of purified DNA-origami structure through AGE is typically laborious because of the post-electrophoresis extraction, desalting and concentration steps. Here, we present a readily scalable purification approach utilizing rate-zonal centrifugation, which provides comparable separation res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
173
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(178 citation statements)
references
References 32 publications
(13 reference statements)
2
173
0
Order By: Relevance
“…It has been shown that multi-origami structures can be successfully separated based on their sizes, for example using glycerol-gradient centrifugation or size-exclusion chromatography. 27,40 A possible concern for applying these methods to separate fractal arrays is that the interactions between origami tiles may be too weak to survive the separation process. To demonstrate that the origami arrays can be strengthened after fractal assembly, we added a 10-fold excess of a full set of 44 edge staples, that each have two stacking bonds, to the 4 by 4 arrays shown in Supplementary Fig.…”
Section: Supplementary Information Research Doi:101038/nature24655mentioning
confidence: 99%
“…It has been shown that multi-origami structures can be successfully separated based on their sizes, for example using glycerol-gradient centrifugation or size-exclusion chromatography. 27,40 A possible concern for applying these methods to separate fractal arrays is that the interactions between origami tiles may be too weak to survive the separation process. To demonstrate that the origami arrays can be strengthened after fractal assembly, we added a 10-fold excess of a full set of 44 edge staples, that each have two stacking bonds, to the 4 by 4 arrays shown in Supplementary Fig.…”
Section: Supplementary Information Research Doi:101038/nature24655mentioning
confidence: 99%
“…However, since the entire research field is constantly growing and developing, it is likely that scaling up of the production and simultaneous knockdown of the price will take place rapidly [3,64]. Very recent examples [65][66][67][68] promisingly show that production quantities of pure DNA origami objects are currently about to upgrade from micro-/milligram scale to gram scale. Today, 1 gram of scaffolded megadalton-sized DNA origamis costs approximately 100,000 $.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Moreover, custom-tailored DNA scaffolds now allow the construction of DNA origami structures of different sizes and are not limited to the frequently used M13 single strand [80]. With the aid of suitable purification methods [81][82][83][84][85], these nanostructures can be prepared in pure forms that provide enhanced sensitivity. DNA, being a biomolecule, also provides an advantage of being biocompatible [86] and can be useful for biosensing in combination with biomimetic approaches.…”
Section: Discussion and Outlookmentioning
confidence: 99%